Panagiotis Dimitrakis, The Secret War in Afghanistan: The Soviet Union, China and Anglo-American Intelligence in the Afghan War - Mr. Majid Mahmood (CISS Insight Journal, 2014)
The book titled “The Secret War in Afghanistan: The Soviet Union, China and Anglo-American Intelligence in the Afghan War” written by Panagiotis Dimitrakis has made a detailed study of recently declassified intelligence archives in order to assess Anglo-American and Soviet Union secret intelligence operations and diplomacy relating to the invasion of Afghanistan and the decade long war that followed. The book’s main theme is about how lack of credible information on intentions, and incorrect and sometimes flawed intelligence analysis shaped the trajectory of the Afghan conflict from 1979-1988. Within this theme, Dr. Dimitrakis tracks the Afghan conflict and unveils Cold War realities that were masked behind the public rhetoric at that time.Much has been written on the Afghan conflict of the 1980s but this book differs on two accounts. First is about new insights about Chinese role and policy in Afghanistan during the conflict based on declassified documents on Chinese intentions. Second is about the extent of detailed assessment and evaluation of contemporary intelligence reports cross referenced with the opponents’ reports and views. Moreover the book is also about how critical intelligence gaps and personal biases within the policy making community can shape the evolution of a conflict in general and covert operations in particular.